Therapeutic kidney donation: a potential source of precious organs. (November 2013) - Khurram, Muhammad Arslan; Wilson, Colin; Vasdev, Nikhil; Manas, Derek; Talbot, David; Rix, David
The number of patients awaiting a renal transplant considerably exceeds the number of organ grafts available. A successful kidney transplant is the most clinically and cost effective treatment for patients with end stage renal disease. A proportion of patients currently die awaiting a renal transplant as their continues to be a global deficiency of renal allografts. Efforts continue to be made in order to improve the current situation of waiting lists and there is now an urgent clinical need to explore potential new sources to increase the number of renal allografts for transplantation. We describe a successful case of a renal transplant with a kidney removed for benign aetiology and transplanted into a patient who was on the cadaveric renal transplant waiting list for 6 years. We predict that this of 'Altruistic domino donation' concept could potentially reduce the waiting list for cadaveric renal transplantation and more importantly become a valuable source for new renal allografts.